The competitive effect of heterogeneous subjects dominant environmental regulations on environmental quality and its asymmetric strategies - He, Xin; Tang, Xinmeng; Liu, Tengyuan; Kholaif, Moustafa Mohamed Nazief Haggag Kotb (Frontiers in Environmental Science, 2025)
IntroductionBased on the heterogeneity of participants, current research generally categorizes environmental regulations into three types, government‐, market‐, and public‐dominant environmental regulations, but neglects their intricate real‐world interactions.MethodsTo bridge this gap, this study employs panel data spanning 30 Chinese provinces from 2010 to 2021, based on employing the introduced synergy intensity variable (HSP_Synergy), the objective is to investigate the combined effects of these regulations on environmental quality and develop an asymmetric political strategy for optimizing environmental benefits.Results and discussionKey findings include: (1) The heterogeneous subjects participation synergy index (HSP_Synergy) effectively integrates diverse heterogenous subjects dominant environmental regulations into a unified research framework. (2) By analyzing the interaction among heterogeneous subjects environmental regulations, using the environmental administrative, environmental tax, and public environmental concern as proxy variables, competitive rather than cooperative effects on environmental quality are identified. An incremental unit of synergy intensity corresponds to a decline of approximately 22%–25% in environmental quality. Notably, regions with lower synergy degrees exhibit 36%–42% higher environmental quality compared to those with higher synergy degrees. (3) This study introduces “asymmetric strategy” as an effective mode for maximizing environmental effects. Introducing both environmental administrative penalty and public environmental concern in environmental management leads to 6%–17% higher environmental benefits compared to introducing environmental administrative penalty and environmental tax, and 21%−23% higher benefits compared to environmental tax and public environmental concern combined participation.